Total quality management practices in the Islamic banking industry : comparison between Bangladesh and Malaysian Islamic bank - Haque, A. K. M. Ahasanul (Center for Research on Islamic Management and Business (CRIMB), 2014)
Abstract Bangladesh, being a Muslim country needs to expedite its Islamic banking services to uphold her Islamic values. This study aimed to provide a deeper understanding of the applicability of TQM in the Islamic banking sector in Bangladesh by identifying and matching as well as comparing (the successful implementation of) the unique factors that affect the applicability of TQM in Malaysian Islamic banks. Malaysia was chosen as Malaysian Islamic banking is considered as the pioneer in Islamic banking sector. Therefore, identifying and examining most established Islamic banking industry would make this study a more consistent, reliable and resourceful one for the Bangladeshi Islamic banking sector. A convenient sampling approach was adopted for sample employees of Maybank Islamic Berhad of Malaysia (MIB) and Islami Bank Bangladesh Limited (IBBL). The data was collected via selfadministered close ended questionnaires distributed to the respondents. Total of 300 questionnaires were distributed (150 each for both the banks) and a total of 203 (86 from Maybank Islamic Berhad and 117 from Islami Bank Bangladesh Limited) completed questionnaire returned which were found valid for further analysis. Results show that the knowledge in the basic principles of TQM practices among the employees in Malaysia is very high in contrast to the relative ignorance of Bangladeshi Islamic banks regarding the practices and implementation of TQM. This study suggests some future actions that need to be carried out within Bangladeshi Islamic banks to improve service quality and productivity.